Molecular docking of antiviral properties of glycosmis pentaphylla (Retz.) Correa - Brinda O P (Centre for Plant Biotechnology and Molecular Biology, College of Horticulture, 2017)
Glycosmis pentaphylla (Retz.) Correa, a tropical shrub, locally known as ‘panal’, is widely used in Ayurveda, for cough, rheumatism, anaemia and jaundice. Although, various parts of this plant are used against different diseases ranging from ulcer to cancer and also as an antiviral agent, there is no scientific evidence for proving its antiviral potential. Molecular docking facilitates the screening of large number of phytocompounds for their capability to interact with and deactivate the disease effecting proteins, within a short period of time. Hence the present study entitled “Molecular docking of antiviral properties of Glycosmis pentaphylla (Retz.) Correa” was undertaken with the objective to characterize the active ingredients in Glycosmis pentaphylla and to identify the compounds offering antiviral properties to this plant, through docking studies. Separate dry samples were prepared from root, stem and leaf and were powdered. The finely ground powder was converted into a hydroalcoholic extract and was concentrated using rotary evaporator. The concentrated extract was subjected to LCMS/MS analysis through outsourcing. The mass to charge ratio obtained through LCMS/MS analysis was compared with the masses of various compounds identified from this plant though literature review. Identified 23 phytochemicals from leaves and 14 from stem and root were subjected for molecular docking against viral protein targets of chikungunya, hepatitis, dengue and influenza using Discovery Studio 4.0. The protein targets were identified on the basis of information provided in the Chikungunya Drug Target Database. Protein targets for other viral diseases were selected based on the literature. Twelve proteins were selected for chikungunya. Two target proteins each were selected for Hepatitis B, hepatitis C and dengue and one for influenza. Suitability of phytocompounds to be developed as a drug was identified by screening with Lipinski’s and Veber’s rule and ADMET analysis. The ligands with good interaction with the protein target were identified based on the minimum difference between CDOCKER energy and CDOCKER interaction energy. Two phytocompounds, isovaleric acid and avicequinone C, have shown acceptable interaction with the protein targets of all selected viral diseases. These two phytocompounds were found to have acceptable ADMET values (out of the seven parameters five were falling in the acceptable range). Isovaleric acid and avicequinone C were able to establish good interaction with majority of protein targets for the selected viral diseases with minimum difference between CDOCKER energy and CDOCKER interaction energy. They were capable to form hydrogen bonds with the involvement of aminoacid residues along with the establishment of good binding energy. The isovaleric acid and avicequinone C molecules with strong capability to interact and deactivate the disease causing proteins are the basis for the antiviral properties of Glycosmis pentaphylla. Futher isolation and purification of these molecules and wet lab analyses on animal models have to be done to develop antiviral drugs from this plant.